A local existence of viscous self-organized hydrodynamic model. (April 2017) - Zhang, Teng-Fei; Jiang, Ning
Abstract: We establish the local existence result of self-organized hydrodynamic model with viscosity in three dimension case, which was proposed in Degond–Liu–Motsch–Panferov's previous work and was left as one open case. Our strategy relies on the suitable symmetrizing the SOH model in spherical coordinates, which enables us to control the commutator arising in the pressure contribution terms during the process of energy estimate.